1994
DOI: 10.1002/cne.903460204
|View full text |Cite
|
Sign up to set email alerts
|

Projections of physiologically defined subdivisions of the inferior colliculus in the mustacbed bat: Targets in the medial geniculate body and extrathalamic nuclei

Abstract: This study examined the output of the central nucleus of the inferior colliculus to the medial geniculate body and other parts of the nervous system in the mustached bat (Pteronotus parnellii). Small deposits of anterograde tracers (horseradish peroxidase, [3H]leucine, Phaseolus vulgaris leucoagglutinin, wheat germ agglutinin conjugated to horseradish peroxidase, or biocytin) were made at physiologically defined sites in the central nucleus representing major components of the bat's echolocation signal. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
86
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 103 publications
21
86
0
Order By: Relevance
“…There is an orderly progression from the highest frequencies located more caudally (59 kHz) to lower frequencies represented more rostrally. Our penetrations, which were angled 5-25°dorsocaudal to ventrorostral, are expected to encounter decreasing best frequencies with increasing depth, as have other studies using similar electrode orientations (Wenstrup et al, 1994;Wenstrup and Grose, 1995). All single units in the present study were recorded at depths of 125-1975 m, consistent with IC recordings of 10 -50 kHz responses in these previous studies using similar electrode angles.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…There is an orderly progression from the highest frequencies located more caudally (59 kHz) to lower frequencies represented more rostrally. Our penetrations, which were angled 5-25°dorsocaudal to ventrorostral, are expected to encounter decreasing best frequencies with increasing depth, as have other studies using similar electrode orientations (Wenstrup et al, 1994;Wenstrup and Grose, 1995). All single units in the present study were recorded at depths of 125-1975 m, consistent with IC recordings of 10 -50 kHz responses in these previous studies using similar electrode angles.…”
Section: Methodssupporting
confidence: 80%
“…Their presence in the auditory midbrain may be understandable in the context of sonar behavior, in which flight adjustments in response to target movement must be made within the 1-2 sec duration of an interception sequence. Projections of the IC to premotor centers could provide highly processed information useful for rapid changes in vocalization or flight (Schweizer, 1981;Frisina et al, 1989;Schuller et al, 1991a;Wenstrup et al, 1994;Casseday and Covey, 1996).…”
mentioning
confidence: 99%
“…The presence of retrogradely labeled cells in the ICx and CNIC in our hemisected midbrain preparation raises the possibility that some of the labeled axons in the SC were fibers of passage originating from these auditory structures. However, the projection from other regions of the IC to the nBIC (Doubell et al 2000;Wenstrup et al 1994) could also account for those retrogradely labeled neurons. Moreover, projections from elsewhere in the IC to the dSC are less likely to be functional in the slices because most of the axons would have been sectioned during the preparation of the slices.…”
Section: Multisensory Circuits In the Slice: Specificity Of Afferent mentioning
confidence: 99%
“…12C), but not in MGd or MGm. Studies in the cat (Kudo and Niimi, 1980) and bat (Wenstrup et al, 1994) have demonstrated that after injections of anterograde tracers in IC, terminal labeling in MGv appears as dense clusters of terminals aligned dorsoventrally, often forming "bands" (Fig. 12 B).…”
Section: Clustering and Eye-specific Segregation Of Retino-mgn Projecmentioning
confidence: 99%